Sosialisasi dan Penanaman Mangrove Bersama Masyarakat Pesisir Desa Sungai Pasir, Kecamantan Lunci, Kabupaten Sukamara - Vita Yanuar (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
One of the regions in Indonesia that has mangrove forests is Sukamara Regency, Central Kalimantan Province. With this location, this Community Service (PKM) will provide outreach regarding the understanding of the residents of Sungai Pasir Village about the Types, Characteristics and Habitat of Mangroves and 2) Planting Mangroves on the Coastal Coast of Sungai Pasir Village, Sukamara Regency. The method used is socialization in providing education to the community on the Coastal Coast of Sungai Pasir Village, Sukamara Regency. The PKM results show that there is cooperation between the community, the village government, representatives of the Watershed and Protected Forest Management Center (BPDASHL) and the Head of the Aquatic Resources Management Study Program, Faculty of Agriculture, Antakusuma University, Pangkalan Bun in preserving Mangroves.